VARIOUS TERMS OF CERTIFICATION PROGRAM LAND MASS , IDE AN IMAGE OR SEIZURE - H. Sudri heryana (JURNAL HUKUM DE'RECHTSSTAAT, 2015)
ABSTRACT People rights enforcement is the duty of the executive officers from the function of government institutions in carrying out its duties and functions. Similarly, Agrarian Institution / BPN in serving the public in the land field of this country.  Remembering its strategic program referred to, in the implementation of agrarian involves officials from the center to the following areas Governor, the Regent, Mayor, Head of sub district and villages officials. Besides to support the success of this activities, also involved the Agricultural Special Teams arrangement involve Opstib membership as a security element which at that time was very well respected in the main settlement of land disputes. PRONA. Prona is a program that can be categorized as a flagship program of Agrarian / BPN service to the people, because as an early breakthrough for the sake of upholding the rights on public land with the concept of fast, accurate and simple. As a national movement, this program is called flagship program remembering in this concept of specificity in service. Keywords: Land Certification, Prona, Scramble Image